Confluent and reticulated papillomatosis successfully treated with azithromycin. - Keklikoğlu, E.N.; Ödemiş, H.; Toprak, M.; Can Kuru, B. (European Journal of Pediatric Dermatology, 2022)
Confluent and reticulated papillomatosis (CRP) is characterized by reticulated hyperkeratotic plaques of uncertain etiology. CRP begins in the upper trunk, and can then spread to the neck, chest, and shoulders. It usually occurs after puberty, the average age being 15, as in the case described in the current report.